Archiv für Reformationsgeschichte - Archive for Reformation History : Internationale Zeitschrift zur Erforschung der Reformation und ihrer Weltwirkungen - An international journal concerned with the history of the Reformation and its significance in world affairs (Gütersloher Verlagshaus, 1904)
The Archive for Reformation History is an international journal which publishes articles relating to aspects of early modern European religious life and thought that touch on the Reformation and Catholic/Counter Reformation movements. The journal is also concerned with the extension of European theology and practice into the extra-European world. Its chronological range is approximately 1450-1650. The Archive for Reformation History is published under the auspices of the Verein für Reformationsgeschichte and the Society for Reformation Research. It appears annually in one volume of articles approximately 320 pages in length and a supplementary volume, Literature Review, approximately 180 pages in length, which consists of brief reviews of a large number of books and articles on aspects of early modern religion and society that appeared in time to be considered. ---------- PRINT available from Gütersloher Verlagshaus:http://www.fachzeitschriften-religion.de/archiv-fuer-reformationsgeschichte-aufsatzband